2020
DOI: 10.1029/2020jg005665
|View full text |Cite
|
Sign up to set email alerts
|

High Vapor Pressure Deficit Decreases the Productivity and Water Use Efficiency of Rain‐Induced Pulses in Semiarid Ecosystems

Abstract: Intermittent rain events drive dynamic pulses of carbon and water exchange in many arid and semiarid ecosystems. Although soil moisture is known to control these pulses, the effect of atmospheric dryness on pulses is not well documented. Here we hypothesized that vapor pressure deficit (VPD) modulates net ecosystem production (NEP) and ecosystem-scale water use efficiency (WUE) during pulse events due to its effects on canopy stomatal conductance and evapotranspiration. We quantified relationships between VPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 92 publications
1
23
0
Order By: Relevance
“…This is presently not the case in this semi-arid region-at six of the seven low elevation sites, vegetation greenness was correlated more with precipitation than with VPD, which may be due to the prevalent isohydric ecosystems in this region. Roby et al [60] found that shrubs dominated by C3 photosynthetic pathways are more sensitive to VPD than grasses dominated by C4 pathways, which agrees with our results. Most of the vegetation in our study region are C3 plants, hence the vegetation greenness interannual variability is more sensitive to precipitation than to VPD.…”
Section: Effects Of Soil Moisture and Atmospheric Humidity On Vegetation Dynamicssupporting
confidence: 93%
“…This is presently not the case in this semi-arid region-at six of the seven low elevation sites, vegetation greenness was correlated more with precipitation than with VPD, which may be due to the prevalent isohydric ecosystems in this region. Roby et al [60] found that shrubs dominated by C3 photosynthetic pathways are more sensitive to VPD than grasses dominated by C4 pathways, which agrees with our results. Most of the vegetation in our study region are C3 plants, hence the vegetation greenness interannual variability is more sensitive to precipitation than to VPD.…”
Section: Effects Of Soil Moisture and Atmospheric Humidity On Vegetation Dynamicssupporting
confidence: 93%
“…We suspect that the smaller Re changes here are due to evaluating pulse behavior during spring and summer months when soil microbes have already largely upregulated following dormancy during the winter months. We ultimately interpret the NEP increases to be due to primary production as seen in previous studies (Roby et al, 2020), though with caution considering uncertainties in partitioning GPP and Re and using nighttime carbon fluxes. Table 1 on each day after rain pulses.…”
Section: Accepted Articlementioning
confidence: 73%
“…Results repeated with FLUXNET‐partitioned GPP show nearly identical results (not shown). Furthermore, previous field studies show that R e tends to increase which would instead decrease NEP immediately after a rain event due to the “Birch effect” (Chen et al., 2009; Huxman, Cable, et al., 2004; Jenerette et al., 2008; Roby et al., 2020; Williams et al., 2009; Xu et al., 2004). Therefore, we interpret the frequent NEP increases as GPP upregulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean annual temperature (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) is approximately 19.0°C, with daytime maximum temperature often exceeding 35°C in June (Scott et al, 2009). The mean annual precipitation (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) is 384 mm, about 50%-60% of which arrives during the summer growing season associated with the North American Monsoon (July-September) (Roby et al, 2020;Scott et al, 2008)…”
Section: Site Descriptionmentioning
confidence: 99%